2010
DOI: 10.1118/1.3375895
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of ionization chamber absorbed dose factors in megavoltage photon beams

Abstract: Based on the experimental evidence obtained here, specification for a reference-class ionization chamber could be developed that would minimize the error in using a dosimetry protocol with calculated beam quality conversion factors. The experimental k(Q) data obtained here for a wide range of thimble chambers can be used when choosing suitable detectors for reference dosimetry and are intended to be used in the upcoming update/addendum to the AAPM TG-51 dosimetry protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
171
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(195 citation statements)
references
References 36 publications
21
171
1
2
Order By: Relevance
“…The results in this study are supported by recent work by McEwen, (16) who reported recombination factors for different chambers as a function of dose per pulse. McEwen's data for an Exradin A‐12 chamber are shown in Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The results in this study are supported by recent work by McEwen, (16) who reported recombination factors for different chambers as a function of dose per pulse. McEwen's data for an Exradin A‐12 chamber are shown in Fig.…”
Section: Discussionsupporting
confidence: 90%
“…32 However, after a 1-kGy warm-up, A26 IC readings showed a 0.2 and 0.1% relative standard deviation for 3 3 3-and 10 3 10-cm 2 fields, respectively. W1 PSD measurements showed a relative standard deviation of 0.1% for both 3 3 3-and 10 3 10-cm 2 fields.…”
Section: Detector Physical Characterizationmentioning
confidence: 99%
“…Although the data obtained here suggest long-term stability of certain chamber types, there are other reasons (e.g., issues with chamber settling to a stable reading or ion recombination behavior as pointed out by McEwen 14 and others) for rejecting the use of these chambers as reference-class detectors. In addition, ion chamber types that do not meet the 0.3% threshold selected as an indicator of stability may still be appropriate for other purposes (e.g., relative dosimetry).…”
Section: Manufacturermentioning
confidence: 76%